GERM-11. TREATMENT AND OUTCOMES OF CENTRAL NERVOUS SYSTEM NON-GERMINOMATOUS GERM CELL TUMORS WITH EARLY RELAPSE DURING INDUCTION CHEMOTHERAPY. Issue 2 (22nd June 2018) - Tran, Hung; Margol, Ashley; Robison, Nathan; Wong, Kenneth; Finlay, Jonathan; Dhall, Girish
Abstract: PURPOSE: Prognosis for central nervous system (CNS) non-germinomatous germ cell tumor (NGGCT) patients that relapse during induction is poor. We present our experience for these patients. METHODS: Medical records of CNS NGGCT patients at Children's Hospital Los Angeles between 2008 and 2014 were reviewed for clinical characteristics, treatment, and outcome. RESULTS: Eight (27.6%) of 29 patients relapsed or were refractory during induction chemotherapy, an average of 6.3 months from diagnosis. Five patients had pineal primaries and three patients had synchronous pineal and suprasellar tumors. All patients had tumor marker (TM) elevation in serum and/or CSF; four patients underwent biopsy. Three patients had local relapse, two local and ventricular, and three had TM-only relapse. All received re-induction chemotherapy with gemcitabine 800mg/m2, paclitaxel 170mg/m2, and oxaliplatin 100mg/m2 (GemPOx). After re-induction, the three TM-only relapses continued to have no evidence of disease (NED) radiographically, three patients showed a partial response (PR), and two patients had stable disease (SD). Seven patients received high-dose chemotherapy with a thiotepa-based regimen followed by autologous stem cell rescue (ASCR). After ASCR, radiographically, three TM positive cases continued to be NED, three had a PR, and one patient had SD. Six received additional irradiation post-transplant, of which five are alive. Six of eight relapsed/refractory patients are alive at 41, 42, 66, 71, 78, 79 months from initial diagnosis. CONCLUSIONS: Relapsed/refractory CNS NGGCT patients can be successfully salvaged by re-induction chemotherapy followed by consolidation with a thiotepa-based myeloablative regimen and re- irradiation.